Olympiads as an Innovative Teaching Method (Texas Journal of Multidisciplinary Studies, 2024)
The use of interactive forms of training in the educational process helps students to develop professional and general cultural competencies. The educational process, based on the use of interactive methods in the teaching process, is organized on the basis of involving all students of the group in mastering the educational material. Joint activity means that during this exercise, each student shares his knowledge, ways of working, makes his individual contribution to solving the situation. By applying pedagogical technology methods in modern lessons, additional information (handouts, tests, problems, riddles, questions and answers, various crosswords, experiments, etc.) should cover the main topic during the lesson. At the end of the lesson, the students will have sufficient knowledge about the scientific information, the place in the field of science and technology development, as well as the encyclopedic scientists who lived in the past. they should also have information about their contributions to the development of this field. For this, it is necessary to use methods of pedagogical technology that are appropriate and convenient for the subject being taught in each lesson. In the implementation of this activity, high pedagogical skills are required from the teacher